2020
DOI: 10.2147/ijgm.s243848
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dyslipidemia and Associated Factors Among Patients Suspected to Have <em>Helicobacter pylori</em> Infection at Jimma University Medical Center, Jimma, Ethiopia</p>

Abstract: Background: Dyslipidemia is a group of plasma lipid and lipoprotein abnormality that is metabolically associated, and it is categorized by low HDL-C and increased LDL-C, TGs, and total cholesterol (TC) levels. Colonization of the stomach by Helicobacter pylori (H. pylori) causes chronic inflammation of the stomach wall which can change some biochemical factors in the patient. On the association of H. pylori infection and its contributions to change in serum lipid profile, different studies reported varying out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
13
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
10
13
2
1
Order By: Relevance
“…On the other hand, the lowest prevalence of dyslipidemia of 5.2% was reported in a study from Ethiopia ( 13 ). The highest percentage of LDL-C data was reported in a study from Ethiopia (79.7%) ( 33 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, the lowest prevalence of dyslipidemia of 5.2% was reported in a study from Ethiopia ( 13 ). The highest percentage of LDL-C data was reported in a study from Ethiopia (79.7%) ( 33 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 84%
“… 23 , 24 But, in contrast with studies done in Jimma and Iraq. 14 , 18 We have found that serum HDL levels of H. pylori- positive dyspeptic patients (37.54 ± 7.98 mg/dL) were significantly lower than negative dyspeptic patients (43.117 ± 7.858 mg/dL). A similar result was reported in studies conducted in Iraq and a meta-analysis was done in Japan.…”
Section: Discussionmentioning
confidence: 92%
“…An altered lipid profile, including an increased LDL level and decreased HDL level, is one of the most important risk factors for atherosclerotic disease. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Patients suffering of H. pylori infection are prone to display an unfavorable pro-atherogenic lipid profile featured by high triglycerides, total cholesterol and LDL-C and decreased HDL-C levels (22,(66)(67)(68)(69). Zhao et al, found that, in addition to the dyslipidemic profile, bilirubin levels were also diminished in H. pylori infected patients (70).…”
Section: H Pylori Infection and Metabolic Diseasesmentioning
confidence: 99%